EVALUATION ON EXTENT CHANGE AND FUTURE DEVELOPMENT OF URBAN LAND USE USING GIS TECHNOLOGY - DongJie GUAN; XueRu ZHANG; HaiFeng Li; Takuro INOHAE; Tadashi NAGAIE; Kazunori HOKAO (International Association of Lowland Technology, 2012)
Based on four phases of land use patterns obtained in 1976, 1987, 1997 and 2005 with integrating spatial technology of geographic information system(GIS), this paper studied the dynamic change and transformation of various land use types in Fukuoka, Japan. Firstly, the characteristics of quantitative and spatial change of land use in the past 29 years were described according to spatial distribution maps, and then changing of land use extent was evaluated by a dynamic change model. The results indicate that the grade value of land use extent was situated between 2 and 4, showing that the land use extent has been transferring from extensive type to urban use type; additionally, change amount and change rate of land use extent were both greater than 0, thus, the land use extent has been situated at a developing stage. Finally, a transfer matrix of Markov was applied to analyze the transferring process of each land use type and to forecast the tendency of future land use change. The forecasting results reveal that area of urban land will continually keep rising at a gradually decreasing speed. Therefore, it will be a long process for land use extent to reach to the urbanization level.